α7 Nicotinic expression and function in human retinal pigment epitheliu cells - Mader, Julieta Ailén (2023)
The α7 nicotinic receptor (nAChR) is one of the most abundant nAChRs in the nervous system and is also present in non-neuronal cells, including immune and epithelial cells. It is involved in cognition, memory, pain, neuroprotection and inflammation and its potentiation has emerged as a therapeutic strategy for neurological, neurodegenerative, and inflammatory disorders. Given that the increase in oxidative stress in retinal pigment epithelial cells contributes to the development of age-related macular degeneration and that α7 activation exerts cell protective effects, we explored the presence and functional relevance of α7 in D407 retinal pigment epithelium cells. By confocal microscopy using the α7 specific antagonist α-bungarotoxin labeled with Alexa 488 and real time-PCR we demonstrated the presence of α7 in these epithelial cells. To simulate the events occurring in age-related macular degeneration, we treated cells with 500 µM ferric ammonium citrate (FAC) for 48 h to induce stress damage and measured reactive oxygen species (ROS) with the fluorescent probe DCFH-DA and cell viability by the MTT assay. FAC treatment resulted in a significant 56 ± 23% increase in ROS levels with respect to the control. To determine if α7 protects against oxidative damage, we exposed cells for 4 h to a specific α7 agonist, PNU-282987, before the FAC treatment. This exposure reduced 29 ± 3% basal levels of ROS. Notably, PNU-282987 exhibited protective effects against the FAC treatment, leading to a reduction of 46 ± 15% in ROS levels when compared to the treated cells. In line with these observations, exposure to the α7 agonist restored the 20% reduction in cell viability induced by FAC. Overall, we demonstrated for the first time the presence of α7 in the D407 cell line, which is a model system for studying various retinal diseases, and its protective role against oxidative damage, a key factor linked to the onset of macular degeneration